Effect of metal oxide fillers in urethane dimethacrylate polymer with glycerol obtained by photopolymerization synthesis - Benites, Ana Beatriz [UNESP]; Alarcon, Rafael T. [UNESP]; Gaglieri, Caroline [UNESP]; Lamb, Katie J.; Bannach, Gilbert [UNESP] (My University, 2020)
Urethane dimethacrylate (UDMA) is a monomer widely used in photopolymerization reactions to produce biomaterials, due to its advantageous properties such as mechanical resistance and relatively low viscosity. However, this monomer is expensive. Reducing the quantity of UDMA monomer required to obtain the final polymer, without losing its main properties, is essential not just in terms of costs but also green chemistry principles. It has been demonstrated that glycerol inclusion into the polymeric matrix during polymerization is one way to achieve this goal. Thus, this work proposes the insertion of glycerol and metal oxide fillers (Al2O3, TiO2, Nb2O5, La2O3 and ZrO2) in the photopolymerization of urethane dimethacrylate, with the aim to study how these effects the degree of conversion, as well as the thermal properties of the final polymer. The thermal properties were evaluated using simultaneous thermogravimetry–differential thermal analysis (TG–DTA) and differential scanning calorimetry (DSC). The degree of conversion/rate of polymerization was calculated using mid-infrared spectroscopy (MIR). The polymers filled with Al2O3, TiO2, Nb2O5 and La2O3 exhibited good conversion values of 87.42, 78.47, 77.64 and 75.51%, respectively. For all polymers synthesized, no significant changes were observed in their thermal stability. Lastly, it is suggested that the incorporation of the oxides in the monomeric mixture correlate to the degree of conversion, with scanning electronic microscopy (SEM) analysis suggesting oxide dispersion interferes with the morphology of the polymer.
Keywords: Degree of conversion; Glycerol; Metal oxides fillers; Photopolymerization; Urethane dimethacrylate